2008
DOI: 10.1111/j.1360-0443.2007.02084.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to the 1944–45 Dutch ‘hunger winter’ and addiction later in life

Abstract: First-trimester prenatal exposure to famine appears to be associated with addiction later in life. The study confirms the adverse influence of severe malnutrition on brain development and maturation, confirms the influence of perinatal insults on mental health in later life and gives rise to great concern about the possible future consequences for the hunger regions in our world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 27 publications
5
47
1
1
Order By: Relevance
“…Impulsive personality traits are also related to executive functioning (25). It is interesting to note that infants who experience undernutrition during fetal life have poorer executive functioning (26,27) and increased vulnerability to addictive disorders (28) and to attention deficit hyperactivity disorder (29). Recent studies demonstrate substantial links between attention deficit hyperactivity disorder and obesity/overweight (30), and suggest that obesity may be seen as the sign of an addictive disorder (31).…”
Section: Iugr and Feeding Impulsivitymentioning
confidence: 99%
“…Impulsive personality traits are also related to executive functioning (25). It is interesting to note that infants who experience undernutrition during fetal life have poorer executive functioning (26,27) and increased vulnerability to addictive disorders (28) and to attention deficit hyperactivity disorder (29). Recent studies demonstrate substantial links between attention deficit hyperactivity disorder and obesity/overweight (30), and suggest that obesity may be seen as the sign of an addictive disorder (31).…”
Section: Iugr and Feeding Impulsivitymentioning
confidence: 99%
“…Lahti et al (2006) reported that small body size at birth may increase the behavioral symptoms of attention deficit hyperactivity disorder (ADHD). Prenatal exposure to famine was reported to increase the risk of schizophrenia (St Clair et al, 2005;Susser et al, 2008), affective disorder (Brown et al, 2000), antisocial personality disorder (Neugebauer et al, 1999) and addiction (Franzek et al, 2008). Experimental evidence should be accumulated to clarify the relationship between perinatal malnutrition and neurological dysfunction including behavioral abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Although diets during the famine were deficient in many macro-and micronutrients, a 2.5 fold increased incidence of neural tube defects has been observed in the cohort, indicating possible folate deficiency in mothers at the time and a possible epigenetic effect of nutritional deficiency in this cohort [253]. The timing of the nutritional insult appears to influence risk, with increased schizophrenia and addiction reported in offspring exposed to the Dutch hunger winter in the first trimester [255,257], whilst increased affective disorders were reported in offspring exposed during the second and third trimesters [256]. The authors proposed that neurodevelopmental events that occur at late gestation, including migration of neurons from ventricular zone to the neocortex and neuronal differentiation [258], could be affected by an insult at this time resulting in disrupted migration or impaired synaptic connections.…”
Section: B Vitamins Epigenetics and Inheritance Of Psychiatric Disormentioning
confidence: 88%
“…Interestingly, there was a 2-fold increased incidence of schizophrenia [255], and increased incidence of major affective disorders (unipolar and bipolar) [256] and addictive disorder especially in men [257] in the Dutch offspring cohort with gestation during the 1944-45 Dutch hunger winter. Although diets during the famine were deficient in many macro-and micronutrients, a 2.5 fold increased incidence of neural tube defects has been observed in the cohort, indicating possible folate deficiency in mothers at the time and a possible epigenetic effect of nutritional deficiency in this cohort [253].…”
Section: B Vitamins Epigenetics and Inheritance Of Psychiatric Disormentioning
confidence: 98%